1991
DOI: 10.1128/jb.173.20.6453-6459.1991
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of flgM, a gene encoding a negative regulator of flagellin synthesis in Salmonella typhimurium

Abstract: The expression of flagellin in Salmonella typhimurium is coupled to the assembly of complete flagella.Mutations which disrupt this coupling define a gene,flgM, which represses the expression of the flagellin genes in strains with mutations in the basal body, switch, or hook flagellar gene (K. L. Gillen and K. T. Hughes, J. Bacteriol. 173:2301Bacteriol. 173: -2310Bacteriol. 173: , 1991. Complementation studies demonstrated that theflgM gene is contained within a 600-bp cloned DNA fragment. Sequence analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
125
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 41 publications
(28 reference statements)
6
125
0
1
Order By: Relevance
“…In the enteric bacteria an intact hook-basal body complex must be assembled before flagellin is expressed (21,36), and genetic studies have demonstrated a hierarchy of flagellar assembly, motility, and chemotaxis gene expression responsible for this structural regulation (13,14,22,23). A negative regulator of flagellin expression, designated FlgM, that is responsible for the coupling of hook-basal body assembly to flagellin expression has been identified in S. typhimurium (13,14).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the enteric bacteria an intact hook-basal body complex must be assembled before flagellin is expressed (21,36), and genetic studies have demonstrated a hierarchy of flagellar assembly, motility, and chemotaxis gene expression responsible for this structural regulation (13,14,22,23). A negative regulator of flagellin expression, designated FlgM, that is responsible for the coupling of hook-basal body assembly to flagellin expression has been identified in S. typhimurium (13,14).…”
Section: Resultsmentioning
confidence: 99%
“…The cF factor of E. coli displays a promoter specificity similar to that of aD and has been shown to transcribe certain flagellar and chemotaxis genes in that organism (3). The gene for the uF factor was identified in S. typhimurium as being thefliA locus (32), part of a class of fla, che, and mot genes termed class II genes (13,14,22,23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It also contains five other genes: flgN,flgM,flgA,flgD, and flgJ. Except for flgM, which codes for an inhibitor of the flagellum-specific sigma factor, u F (2,23), and flgN, which has an unknown function (3), these genes are thought to be related to hook-basal body formation (26,27). Assembly is blocked at the stage of hook protein polymerization inflgD mutants and at the stage of outer-ring formation in flgA mutants (15).…”
mentioning
confidence: 99%